RELATIONS GROUND-VEGETATION IN THE FORMATIONS WITH JUNIPERUS PHOENICEA, AND PINUS HALEPENSIS IN THE MATORRALS OF THE MOSTAGANÉMOIS LITTORAL - Noreddine, Lahouel; Noury, Benabadji; Djamel, Benmansour (European Scientific Journal, ESJ, 2014)
In the present work we have been able to verify the utility of splitting the organic matter that seems to be indispensable, especially when it comes to soil humus and very little polymer containing a large proportion of nondecomposed organic matter. The study even if it remains incomplete, however, provides some useful information. The work in question reflects the fundamental influence exerted by organic matter as soil and as a driving force behind its dynamic. Humus factor in the vocation of a soil can promote or remove certain plant species. The statistical analysis shows that among other humification of organic matter is fast on substrate sandstone limestone (Calabrien) as a substrate Tithonique Upper Cretaceous which can be explained by the very high rate of humic acids that the substrate sandstone limestone. At the level of plant organic matter provided by mixedwoods (Eucalyptus, Pinus halepensis, Juniperus phoenicea) with a sub made of wood (Retama monosperma, Calycotome spinosa, Pistacia lentiscus, Phylaria latifolia, Lavandula stoecka) has a very good humification with a predominance of humic acids that indicate accelerating the training complex humic clay and a wealth of permanent energy reserves. This concept therefore place humus as predominant factor in the vocation of a soil, humus and a determined will not promote a rather limited number of plant species.